Cold-standby Redundancy Optimization for Multi-Type Production Systems Using NSGA-II - Wang, Wei; Xu, Yaofeng; Wei, Jiqing; Qu, Wei (2018 IEEE International Conference on Industrial Engineering and Engineering Management (IEEM), 2018)
This paper develops a new model for investigating cold-standby redundancy allocation problem (RAP) of a multi-type production system. The system consists of several independent linearly ordered subsystems which undertaking different tasks. The system can process different types of production. Each type of production requires a unique manufacturing line: required subsystems should be turned on, while others powered off. A binary matrix is used to describe the structure of multi-type production system. Cold-standby redundancy on subsystems is considered for achieving higher reliabilities of the different manufacturing lines. The RAP for the multi-type production system is essentially multi-objective subject to resource constraints. The paper formulates the multi-objective problem and solves it by using a well-known algorithm called NSGA-II. Finally, illustrative examples are presented.